A Study on the Voices of Resistance in Korean Poetry under Japanese Colonial Rule - Oleksiuk, Marlena (International Journal of Korean Humanities and Social Sciences, 2025)
The Japanese occupation of Korea (1910–1945) marked one of the darkest periods in the nation’s history, as Koreans endured political repression, cultural suppression, and constant fear under colonial rule. Beyond the physical struggles of survival–forced labor, sexual slavery, and the eradication of the Korean language–Koreans sought alternative forms of resistance. Among the most powerful of these was literature. This paper examines how prominent writers such as Yi Sang, Yi Sanghwa, Yi Yuksa, Yoon Dongju, Kim Sowol, and Yi Hyoseok used poetry and prose to express resistance, preserve cultural identity, and sustain hope for independence. Although these writers did not live to witness liberation, their works became enduring voices of defiance and continue to shape the cultural memory of modern Korea (Lee Peter H. 1974:161-193).